Guardians of abundance: aerial application, agricultural chemicals, and toxicity in the postwar prairie west - Vail, David Douglas (Kansas State University, 2012)
This dissertation contributes to the environmental, agricultural, and technological history of the modern United States by examining pesticide use and the debates surrounding them in the Great Plains from the 1940s to the 1980s. Specifically, it addresses the relationships among aerial sprayers, farmers, agriculturalists, and grassroots concepts of toxicity that emerged from mid-century technological and environmental changes. It argues that pesticides as well as a variety of weeds and insects actively transformed the tools, attitudes, and regulatory policies of their users. Historians of agricultural chemical use in America have focused on the political debates over DDT, the social activism against pesticides that Rachel Carson inspired with her best-selling book Silent Spring (1962), the growth in federal regulatory policy in the 1970s, and the contentious reactions by the chemical and agricultural industries. This study offers a new, ground-level history of pesticides by showing how aerial sprayers, farmers, and agriculturalists developed custom chemical applications and conceptualized toxicity as each related to the technological and environmental changes in the region. Drawing on multiple sources, including agricultural experiment station reports, scientific studies, government documents, farm journals, landowner and aerial spray pilot correspondence, and oral histories, this study explores how local producers changed with their chemicals, spray planes, and pests to develop an environmental ethos that understood toxicity as a synthetic and natural danger. Although opposition to pesticides became central to modern environmentalism, debates around pesticides‘ effectiveness and dangers did not come only from activists or government regulators. Beginning just after World War II, landowners and spray pilots in the fields and rural airstrips of the Great Plains took the hazards of agricultural chemicals seriously, critiquing how and why pesticides were used for decades after. By viewing chemicals, spray planes, and pests, as well as landowners, pilots, and agriculturalists as equal forces in the regional transformation of farming landscapes, this dissertation highlights a new history of pesticides, agriculture, and the environment. Farmers and custom applicators did not simply follow the economic goals of agribusiness. Nor did they dismiss the dangers of pesticides. Rather, they constructed their own standards of injury and environmental risk that stressed accuracy, regulation, and a reasonable certainty of safety—a result of the equally transformational influences of chemicals, pests, and the region. This study finally offers new insights into the creation of national chemical policy and the regulatory debates over pesticides during the 1960s and 1970s.
Keywords: Pesticides; Aerial Spraying; Agriculture; Toxicity; Great Plains; Weed Science; Agriculture, General (0473); American History (0337); History (0578)